UMPSA conducts International Community Service Programme through AR and VR at Tadika Islam Mutiara Amaliyah Medan - Mohd Shahri, Mohd Akhir (UMPSA, 2025)
MEDAN, 18 September 2025 – The Flexible Learning & Micro-Credential Centre (FLEXMC), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), successfully implemented an International Community Service Programme with 33 students of Tadika Islam Mutiara Amaliyah in Medan, Indonesia.